MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS MELALUI PENGGUNAAN MEDIA KARTU GAMBAR PADA SISWA KELAS VII SMPN 1 MUARA BUNGO - Yesi Novianti (Jurnal Muara Pendidikan, 2020)
The mastery of English vocabulary in class VII.4 at SMPN 1 Muara Bungo is still low. This study aims to describe the use of picture card media to improve the mastery of English vocabulary in grade VII.4 students of SMPN 1 Muara Bungo. This research is a kind of classroom action research with 29 students as the research subjects. The study design was carried out in two cycles. Each cycle of action consists of planning, treatment, observation and reflection. Data collection instruments using observation sheets, questions, and field notes sheets. Data analysis uses quantitative and qualitative descriptive analysis. The results showed that (1) the use of picture card media can improve the mastery of English vocabulary on aspects of reading vocabulary and pronouncing vocabulary. Besides helping students to read vocabulary individually in groups well. (2) The use of picture card media can improve the mastery of English vocabulary. This is indicated from the test results increasing by 17.2% in the first cycle, and the completeness of the students' test results in the second cycle increased by 17.3%.